By-Products of Fruit and Vegetables: Antioxidant Properties of Extractable and Non-Extractable Phenolic Compounds - Yu Zeng; Wenyi Zhou; Jiahao Yu; Lei Zhao; Kai Wang; Zhuoyan Hu; Xuwei Liu (MDPI AG, 2023)
Non-extractable phenolic compounds (NEPs), or bound phenolic compounds, represent a crucial component of polyphenols. They are an essential fraction that remains in the residual matrix after the extraction of extractable phenolic compounds (EPs), making them a valuable resource for numerous applications. These compounds encompass a diverse range of phenolic compounds, ranging from low molecular weight phenolic to high polymeric polyphenols attached to other macro molecules, e.g., cell walls and proteins. Their status as natural, green antioxidants have been well established, with numerous studies showcasing their anti-inflammatory, anti-aging, anti-cancer, and hypoglycemic activities. These properties make them a highly desirable alternative to synthetic antioxidants. Fruit and vegetable (F&Veg) wastes, e.g., peels, pomace, and seeds, generated during the harvest, transport, and processing of F&Vegs, are abundant in NEPs and EPs. This review delves into the various types, contents, structures, and antioxidant activities of NEPs and EPs in F&Veg wastes. The relationship between the structure of these compounds and their antioxidant activity is explored in detail, highlighting the importance of structure-activity relationships in the field of natural antioxidants. Their potential applications ranging from functional food and beverage products to nutraceutical and cosmetic products. A glimpse into their bright future as a valuable resource for a greener, healthier, and more sustainable future, and calling for researchers, industrialists, and policymakers to explore their full potential, are elaborated.